Dinámica poblacional del psílido asiático en el nordeste de Entre Ríos - Pierotti, Justina Maria; Jiménez, Nadia L.; Sánchez-Restrepo, Andrés F.; Logarzo, Guillermo; Bouvet, Juan Pedro (Asociación Argentina de Ecología (AsAE), 2024)
Póster